The risk of malaria in Ghanaian infants born to women managed in pregnancy with intermittent screening and treatment for malaria or intermittent preventive treatment with sulfadoxine/pyrimethamine. (December 2016) - Awine, Timothy; Belko, Mark; Oduro, Abraham; Oyakhirome, Sunny; Tagbor, Harry; Chandramohan, Daniel; Milligan, Paul; Cairns, Matthew; Greenwood, Brian; Williams, John
Abstract Background Several studies have reported an association between malaria infection of the placenta and the risk of malaria in young children in the first year of life, but it is not known if this is causal, or influenced by malaria control measures during pregnancy. This paper compares the incidence of malaria in infants born to mothers who received either intermittent preventive treatment with sulfadoxine/pyrimethamine (IPTp-SP) or screening with a rapid diagnostic test and treatment with artemether–lumefantrine (ISTp-AL) during their pregnancy. Methods From July 2011 to April 2013, 988 infants of women enrolled in a trial of IPTp-SP versus ISTp-AL in the Kassena-Nankana districts of northern Ghana were followed to determine the risk of clinical malaria during early life, and their risk of parasitaemia and anaemia at 6 and 12 months of age. In addition, the incidence of clinical malaria in infants whose mothers had malaria infection of the placenta was compared with that in infants born to women free of placental malaria. Results The incidence of clinical malaria was 0.237 and 0.211 episodes per child year in infants whose mothers had received ISTp-AL or IPTp-SP, respectively. The adjusted incidence rate ratio and the adjusted rate difference were 0.94 (95 % CI 0.68, 1.33) and 0.029 (95 % CI −0.053, 0.110) cases per child year at risk respectively. The incidence of clinical malaria was similar in infants born to women with placental malaria (0.195 episodes per child year) and in infants of women without placental malaria (0.224 episodes per child year) (rate ratio = 0.86 [95 % CI 0.54, 1.37]). Conclusion Infants born to women managed with ISTp-AL during pregnancy were not at greatly increased risk of malaria compared with infants born to women who had received IPTp-SP. The incidence of malaria in infants was similar whether or not their mother had had placental malaria.